Rotator Cuff Lesions in Patients with Stiff Shoulders: A Prospective Analysis of 379 Shoulders. (5th August 2015) - Ueda, Yusuke; Sugaya, Hiroyuki; Takahashi, Norimasa; Matsuki, Keisuke; Kawai, Nobuaki; Tokai, Morihito; Onishi, Kazutomo; Hoshika, Shota
Abstract : Background: Idiopathic adhesive capsulitis is defined as a frozen shoulder with severe and global range-of-motion loss of unknown etiology. The purpose of our study was to clarify the prevalence of rotator cuff lesions according to patterns and severity of range-of-motion loss in a large cohort of patients with stiff shoulders. Methods: Rotator cuff pathology was prospectively investigated with use of magnetic resonance imaging (MRI) or ultrasonography in a series of 379 stiff shoulders; patients with traumatic etiology, diabetes, or radiographic abnormalities were excluded. Eighty-nine shoulders demonstrated severe and global loss of passive motion (⩽100° of forward flexion, ⩽10° of external rotation with the arm at the side, and internal rotation not more cephalad than the L5 level) and were classified as having severe and global loss of motion (Group 1). The remaining 290 shoulders were divided into two groups: those with severe but not global loss (Group 2; 111 shoulders) and mild to moderate limitation (Group 3; 179 shoulders). Results: Among all shoulders, imaging demonstrated an intact rotator cuff in 51%, a full-thickness tear in 35%, and a partial-thickness tear in 15%. In Group 1, 91% had an intact rotator cuff and 9% had a partial-thickness rotator cuff tear. No patient in this group demonstrated a full-thickness tear. In Group 2 and Group 3, respectively, 44% and 35% of the shoulders were intact, 17% and 16% had a partial-thickness tear, and 39% and 50% had a full-thickness tear. Conclusions: Shoulder stiffness with severe and global loss of passive range of motion is not associated with full-thickness rotator cuff tears, although some patients may have a partial-thickness tear. Shoulders with severe and global loss of range of motion at a first visit are likely to be cases of idiopathic adhesive capsulitis and may not require further imaging studies.